2017
DOI: 10.1515/romneu-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Ozone therapy – a rare and avoidable source of infectious pathology of the spine

Abstract: Ozone therapy is considered by many as an effective therapy for spinal degenerative pathologies. Despite its possible favorable results, we present a series of serious infectious complications, clearly related to ozone therapy and their treatment. The authors discuss their results compared with the literature and advocate for prudence when recommending ozone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In two of the aforementioned trial, no complications were demonstrated in either group (ozone vs. control), while in one trial, a low incidence of complications was noted with no significant difference between ozone treatment and the non-ozone control group. However, neurosurgeons should give significant attention to ozone therapy as some serious infectious events, related to ozone infiltration, have been demonstrated in several studies ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In two of the aforementioned trial, no complications were demonstrated in either group (ozone vs. control), while in one trial, a low incidence of complications was noted with no significant difference between ozone treatment and the non-ozone control group. However, neurosurgeons should give significant attention to ozone therapy as some serious infectious events, related to ozone infiltration, have been demonstrated in several studies ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 The central issue I addressed is the promotion of ozone therapy treatments by the Brazilian public health system, despite their not being approved by the Brazilian National Health Surveillance Agency (ANVISA). The cautious stance of Brazilian medical organizations as well as the recommendation of the US FDA (Food and Drug Administration) against ozone therapy (including relevant risks) 3 corroborate the need for a debate based on scientific evidence. One article cited by Dr Chirumbolo, discussing a possible treatment of multiple sclerosis with ozone states that “ Further investigations are required to corroborate … ” 4 and describes this gas as “toxic and irritating”.…”
mentioning
confidence: 89%
“…However, some other complications have been reported in the literature, most of them due to malpractice or without a causal relationship between the ozone administration and the adverse event ( Marchetti and La Monaca, 2000 ; Corea et al, 2004 ; Lo Giudice et al, 2004 ; Ginanneschi et al, 2006 ; Gazzeri et al, 2007 ; Bo et al, 2009 ; Seyman et al, 2012 ; Vilas-Rolan et al, 2012 ; Fort et al, 2014 ; Menéndez et al, 2014 ; Mustafa et al, 2015 ; Vanni et al, 2015 ; Cano et al, 2016 ; Salvatore et al, 2016 ; Balan et al, 2017 ; Hüseyin et al, 2017 ; Wen-Juan et al, 2017 ; Beyaz et al, 2018 ; Yang et al, 2018 ; He et al, 2019 ). Most of them disappeared in a few days not needing specific medical treatment.…”
Section: Safety and Contraindications Of Ozone Therapymentioning
confidence: 99%